Knowledge about HIV/AIDS among First Year Medical Students - Rekha Udgiri; M.C. Yadavannavar; M.M. Angadi; Sharvanan E (Al Ameen Journal of Medical Sciences, 2011)
Objectives: To study the awareness and knowledge about HIV/AIDS among the students. Material and Methods: A Cross sectional study was done among 141 students. The information was collected form them within 2-3 weeks of admission using pre-test semi structured questionnaire. Result: All students were aware of AIDS in terms of its definition and modes of transmission. About prevention and cure no significant difference was found between boys & girls. Conclusion: Incomplete knowledge about sign & symptoms of HIV/AIDS among the respondents.